A global meta-analysis of greenhouse gases emission and crop yield under no-tillage as compared to conventional tillage - Shakoor, Awais; Shahbaz, Muhammad; Farooq, Taimoor Hassan; Sahar, Najam E.; Shahzad, Sher Muhammad; Altaf, Muhammad Mohsin; Ashraf, Muhammad (The Science of the total environment, 2021)
No-tillage (NT) practice is extensively adopted with aims to improve soil physical conditions, carbon (C) sequestration and to alleviate greenhouse gases (GHGs) emissions without compromising crop yield. However, the influences of NT on GHGs emissions and crop yields remains inconsistent. A global meta-analysis was performed by using fifty peer-reviewed publications to assess the effectiveness of soil physicochemical properties, nitrogen (N) fertilization, type and duration of crop, water management and climatic zones on GHGs emissions and crop yields under NT compared to conventional tillage (CT) practices. The outcome reveals that compared to CT, NT increased CO2, N2O, and CH4 emissions by 7.1, 12.0, and 20.8%, respectively. In contrast, NT caused up to 7.6% decline in global warming potential as compared to CT. However, absence of difference in crop yield was observed both under NT and CT practices. Increasing N fertilization rates under NT improved crop yield and GHGs emission up to 23 and 58%, respectively, compared to CT. Further, NT practices caused an increase of 16.1% CO2 and 14.7% N2O emission in the rainfed areas and up to 54.0% CH4 emission under irrigated areas as compared to CT practices. This meta-analysis study provides a scientific basis for evaluating the effects of NT on GHGs emissions and crop yields, and also provides basic information to mitigate the GHGs emissions that are associated with NT practice. [Display omitted] •Fifty peer-reviewed publications were used to conduct a global meta-analysis.•No-tillage (NT) significantly increased CO2, N2O, and CH4 emissions by 7.14%, 11.96%, and 20.80%.•Overall, NT significantly reduced GWP by 7.56% as compared to (conventional tillage) CT.•In NT, barley and wheat yields increased by 43.76% and 4.49%, respectively.